Zoogeomorphology animals as geomorphic agents - Butler, David R. (Cambridge University Press, 1995)
Animals as geomorphic agents have primarily been considered curiosities in the literature of geomorphology, whose spatial and quantitative influences have been seen as both limited and minor. Zoogeomorphology: Animals as Geomorphic Agents, which is wholly devoted to this topic, examines the distinct geomorphic influences of invertebrates, ectothermic vertebrates, birds and mammals, and demonstrates the importance of animals as landscape sculptors. Specific processes associated with the diversity of animal influences in geomorphology are examined, including burrowing and denning, nesting, lithophagy and geophagy, wallowing and trampling, food caching, excavating for food, and dam building by beavers. Particular emphasis is placed on terrestrial animals, although aquatic animals are also discussed where appropriate.